The Returns to Innovation in East Asia : The Role of the Business Environment and Firms' Characteristics - de Nicola, Francesca; Chen, Pinyi (World Bank, Washington, DC, 2022)
The paper studies the relationship between innovation efforts, innovation outputs, and productivity, using firm-level data from six East Asian countries. Firms are more likely to invest in innovation when they use technology licensed by a foreign company, are part of a large group, and have a more educated workforce. Investment in research and development can significantly boost both product and process innovation. Product innovation yields significant productivity gains. However, productivity gains from process innovation are not detectable in the sample.